Field trial on the efficacy of a new fenbendazole/praziquantel combination against nematodes and cestodes of dogs - HIMONAS (Χ. ΧΕΙΜΩΝΑΣ), C.; SOTIRAKI (Σ. ΣΩΤΗΡΑΚΗ), S.; PAPADOPOULOS (Η. ΠΑΠΑΔΟΠΟΥΛΟΣ), E.; PFISTER, K. (Journal of the Hellenic Veterinary Medical Society, 2018)
The gastrointestinal parasitism of dogs and cats due to nematodes and cestodes is particularly common. In most cases animals are infected with both groups of parasites. The control of such mixed infections is carried out with nematocidal and cestocidal drugs administered either separately or combined. The aim of this study was to investigate the efficacy of a new fenbendazole/praziquantel (CANIQUANTEL PLUS®) combination against nematodes and cestodes of dogs. Toward this end 30 naturally infected dogs were divided into 2 groups: one (n=20) was treated with 50mg fenbendazole and 5mg praziquantel/kg b.w. for two consecutive days and the other (n=10) was not treated and served as the control group. Faecal examinations were carried out on the day of treatment as well as 10 days later. The efficacy level of this combined drug was found to be 98.2% and no adverse reactions were observed. It is concluded that, this anthelmintic combination may be safely used for the satisfactory control of mixed gastrointestinal parasitic infections in dogs.